Art and Identity in the Parish Communities of Late Medieval Kent - Ford, Judy Ann (Studies in church history, 1992)
Historians have long been aware that patronage is a crucial factor in interpreting the social meaning of art. The late Middle Ages knew a variety of patrons, each employing art to communicate different sorts of concern: royal and aristocratic courts emphasized political messages, urban communes created governmental myths, cathedrals and monasteries gave expression to spiritual ideas—and all used art to convey notions of social identity. Recent investigations into the process of choosing and procuring works of art in these contexts have not only added perspective to formal art criticism, they have also deepened our understanding of the groups interested in the creation of art. One area in which questions of patronage could perhaps be better illuminated is the community of the parish. The parish served as the primary religious community for the majority of men and women for most of the Middle Ages. It was complex in composition, involving both laity and clergy, encompassing other religious associations, such as gilds, and including the devout and the indifferent, the orthodox and the dissenters.